Peranan Biopestisida Terhadap Penyakit Tanaman Padi Di Desa Hutagaol Peatalun Balige - Nuraida Nuraida; Asmara Sari Nasution (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
Hutagaol Peatalun Village is one of Villages in Balige District Toba Samosis Subdidistrict. Hutagaol Peatalun village is one of the rice agriculture centre in Sumatera Utara.in developing agriculture, farmers have problems about rice disease, that’s blast disease,. To face the problem, farmer should be given solution to help farmer improving biopesticide that have active substance of trichoderma to resolve blast disease. To date, the impact of blast disease was decrease and loss farmer’s rice production. The activity was involving two agriculture group. This activity consist of socialization  and practice to improve  trichoderma  biopesticide in corn media. The result of biopesticide was used by both of agriculture groups directly. This dedication activity succeed to increase farmer’s knowledge skill, and the point of view about  biopesticide as the substitution of chemistry fungicide that always  used by farmer’s.